Hydrogel composites loaded with plant extract as an antibacterial and quorum sensing inhibiting wound dressing. - Baranda, Marivic Masangcay
Delayed wound healing is often caused by bacterial infection. Furthermore, the persistent inflammation brought by the formation of biofilm via quorum sensing causes pain and discomfort. In a novel effort, this study fabricated an antibacterial and quorum sensing inhibiting hydrogel dressing loaded with plant extracts. KC-PVP hydrogel composites were loaded separately with 1 g/mL C. longa and H. durvillei extract under optimized conditions. The hydrogels were characterized through swelling test and FTIR analysis. It was determined that C. longa-loaded and H. durvillei¬-loaded hydrogels have a maximum swelling capacity of 175% and 135%, respectively. The antibacterial efficacy and the quorum sensing inhibition activity of extract-loaded hydrogels were evaluated using soft-layer agar well diffusion method. Hydrogel loaded with C. longa extract displayed 47.0 (±1.0), 45.0 (±1.0) and 32.33 (±0.58) mm mean growth inhibition against S. aureus, E. coli, and P. aeruginosa, respectively. H. durvillei extract-loaded hydrogels inhibited the growth of S. aureus, E. coli, and P. aeruginosa by 45.33 (±0.58). 43.67 (±1.52), and 33.33 (±0.58) mm in diameter, respectively. The quorum sensing inhibition zone of C. longa extract and H. durvillei extract-loaded hydrogels were 49.63 (±0.40) and 49.37 (±1.11) mm diameter, respectively. Overall, the extract-loaded hydrogel composites exhibited good antibacterial and quorum sensing inhibiting activity potentially for wound treatment.